A Pooled Analysis of Robotic Versus Laparoscopic Surgery for Total Mesorectal Excision for Rectal Cancer. Issue 3 (June 2016) - Wang, Yue; Zhao, Guo-Hua; Yang, Helen; Lin, Jie
Abstract : Objective: We conducted the meta-analysis to evaluate the safety and efficacy of robotic total mesorectal excision (RTME) compared with laparoscopic total mesorectal excision (LTME) in treatment of rectal cancer. Materials and Methods: A systematic search of Medline, Embase databases, and the Cochrane Library was performed to identify studies that compared RTME versus LTME for rectal cancer and were published up to July 2014. The methodological quality of the selected studies was assessed. Depending on statistical heterogeneity, the fixed or random effect model was used for the meta-analysis. Outcomes of interest and related outcomes were evaluated. Results: Eight studies were included in the meta-analysis. These studies involved a total of 1229 patients, 554 of whom underwent RTME and 675 of whom underwent LTME. The meta-analysis showed that RTME had lower conversion rate and positive rate of circumferential resection margins, and lesser incidence of erectile dysfunction. Conclusions: Our study suggests that RTME for rectal cancer appears to be a safe, feasible, and minimally invasive alternative to its laparoscopic counterpart. But the long-term outcomes between the 2 techniques need to be further examined.